Molecular insights into mineralotropic hormone inter-regulation - Pike, J. Wesley; Lee, Seong Min; Meyer, Mark B. (Frontiers in Endocrinology, 2023)
The regulation of mineral homeostasis involves the three mineralotropic hormones PTH, FGF23 and 1,25-dihydroxyvitamin D3 (1,25(OH)2D3). Early research efforts focused on PTH and 1,25(OH)2D3 and more recently on FGF23 have revealed that each of these hormones regulates the expression of the other two. Despite early suggestions of transcriptional processes, it has been only recently that research effort have begun to delineate the genomic mechanisms underpinning this regulation for 1,25(OH)2D3 and FGF23; the regulation of PTH by 1,25(OH)2D3, however, remains obscure. We review here our molecular understanding of how PTH induces Cyp27b1 expression, the gene encoding the enzyme responsible for the synthesis of 1,25(OH)2D3. FGF23 and 1,25(OH)2D3, on the other hand, function by suppressing production of 1,25(OH)2D3. PTH stimulates the PKA-induced recruitment of CREB and its coactivator CBP at CREB occupied sites within the kidney-specific regulatory regions of Cyp27b1. PKA activation also promotes the nuclear translocation of SIK bound coactivators such as CRTC2, where it similarly interacts with CREB occupied Cyp27b1 sites. The negative actions of both FGF23 and 1,25(OH)2D3 appear to suppress Cyp27b1 expression by opposing the recruitment of CREB coactivators at this gene. Reciprocal gene actions are seen at Cyp24a1, the gene encoding the enzyme that degrades 1,25(OH)2D3, thereby contributing to the overall regulation of blood levels of 1,25(OH)2D3. Relative to PTH regulation, we summarize what is known of how 1,25(OH)2D3 regulates PTH suppression. These studies suggest that it is not 1,25(OH)2D3 that controls PTH levels in healthy subjects, but rather calcium itself. Finally, we describe current progress using an in vivo approach that furthers our understanding of the regulation of Fgf23 expression by PTH and 1,25(OH)2D3 and provide the first evidence that P may act to induce Fgf23 expression via a complex transcriptional mechanism in bone. It is clear, however, that additional advances will need to be made to further our understanding of the inter-regulation of each of these hormonal genes.